2014
DOI: 10.1007/s00213-014-3527-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the structure of drinking, cart expression and dopamine turnover between polydipsic and non polydipsic rats in the quinpirole model of psychotic polydipsia

Abstract: Microstructure analysis confirms that QNP acts on the appetitive component of drinking behavior, making it compulsive. CART expression reduction in response to dopaminergic hyperstimulation might sustain excessive drinking in PD rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Several studies have evidenced the involvement of the dopaminergic system in SID. Both dopaminergic neuron lesions and the administration of dopamine antagonists—haloperidol, clozapine and pimozide—reduced already acquired SID and affected SID development (Didriksen et al 1993 ; Mittleman et al 1994 ; Mittleman and Valenstein 1986 ; Snodgrass and Allen 1989 ), whereas the dopamine D2/3 receptors agonist quinpirole increased this nonregulatory drinking behaviour in rats (Schepisi et al 2014 ). It has been also demonstrated that high drinker rats showed higher dopamine D2 receptor binding than low drinkers in the SID procedure (Pellón et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evidenced the involvement of the dopaminergic system in SID. Both dopaminergic neuron lesions and the administration of dopamine antagonists—haloperidol, clozapine and pimozide—reduced already acquired SID and affected SID development (Didriksen et al 1993 ; Mittleman et al 1994 ; Mittleman and Valenstein 1986 ; Snodgrass and Allen 1989 ), whereas the dopamine D2/3 receptors agonist quinpirole increased this nonregulatory drinking behaviour in rats (Schepisi et al 2014 ). It has been also demonstrated that high drinker rats showed higher dopamine D2 receptor binding than low drinkers in the SID procedure (Pellón et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The precise quantification of the temporal distribution of ILI's may be broadly informative to numerous areas of research including addiction (Barkley‐Levenson and Crabbe, 2012, 2015; Eastwood et al, 2014; Robinson and McCool, 2015), mental illness (Hartfield et al, 2003; Galistu et al, 2011; Schepisi et al, 2014) and aging (Zhang et al, 2008). However, the use of licking microstructure is perhaps most readily translatable for animals models of obesity.…”
Section: Relevance For Study Of Obesity In Animal Modelsmentioning
confidence: 99%
“…13) To explain the development of psychogenic polydipsia in schizophrenia, in an animal model, repeated treatment with D2/D3 agonist quinpirole was shown to induce hyperdipsia 14) in a compulsive manner. 15) Many of the behavioral abnormalities seen in BD may be related to hyperdopaminergic activity, 16) especially in the mesolimbic pathway, 17) which might constitute the basis for hyperdipsia in BD as well. In agreement with this, all of our patients responded to antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%